Involuntary emotional expression disorder (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Involuntary emotional expression disorder (IEED) is an affect disturbance caracterized by a difficulty of controlling emotional expression, that is presented as short, stereotyped and uncontrollable episodes of laugh-ter, crying, or both. This disorder is associated to multiple encephalic pathologies, in many anatomical locations. OBJECTIVES: The aims of this review are to describe the clinical, epidemiological and pathophysiological features of IEED and present an overview of current and future treatment approaches. METHODS: Research on databases such as MEDLINE/PUBMED and LILACS, using the terms involuntary emotional expression disorder, pseudobulbar affect, pathological laughter and crying, stroke, Alzheimer's disease, multiple sclerosis, amyotrophic lateral sclerosis. RESULTS: Episodes of laughing and crying that occurs in involuntary emotional expression disorder besides being uncontrollable,they are also disproportionate to motivating stimulus, and they can even be completly dissociated from the patient's mood or even contraditory to the context to which stimuli occurs. Other terms have been used in the nosography of this disorder, like pseudobulbar affect, pathological laughter and crying, emotional lability, emotionalism and emotional dysregulation. Terms such as forced crying, involuntary crying, pathological emotionality and emotional incontinence have also been used, although less frequently. At the present, specific pathophysiological mechanisms of this disorder are still not clear. Insults that can lead to it are widely spread in the brain, but generaly they involve frontal cortex, the limbic system, the brainstem, the cerebellum and the underlying white matter that interconnect these networks. The most important differential diagnosis is depression. Nowadays, the available pharmacological therapies are based on selective serotonin reuptake inhibitors, tricyclic antidepressants, and, less often, dopaminergic agents. AVP-923 is a new compound that has been researched as a possible future specific treatment. DISCUSSION: Although IEED has long been recognized, even under diverse nomenclature, it remains underdiagnosed. Considering the deleterious effects of this disorder on social, occupational and familiar functionning of the affected patient, its recognition and accurate procedure are decisive to allow an improvement on patient's quality of life.